Peningkatan Omset Penjualan Kelompok Pengrajin Keset melalui Online Marketing - Nathasa Pramudita Irianti; Rizki Dwi Aprilia Susanti; Odhitya Desta Triswidrananta; Elita Mega Selvia Wijaya (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
This program is carried out to increase the income of the "Mekar" women group in Sidoluhur Village, Lawang District, Malang. The "Mekar" women's group is a women's group of equality craftsmen made from patchwork. One of the obstacles they experienced was marketing constraints. Product marketing that has been carried out so far is only done conventionally by entrusting their products in several markets around the villages of Sidoluhur and Lawang. Therefore, an integrated marketing network effort is one of the efforts in increasing the sales turnover of this women's equality group. Efforts are made by providing assistance and training to this group to be activated in marketing products online. Online marketing starts by creating a social media account, selling in the market, then completing it by purchasing online marketing, and finally how to maximize sales on online marketing. Through assistance provided, “Mekar” women's groups that produce equality has been able to increase sales turnover by using online marketing. This increase in sales turnover reached 50%. Understanding the marketing concept of "Mekar" women's groups which were originally only conventional has been developed for online marketing.DOI: https://doi.org/10.26905/abdimas.v6i1.4819